PENGELOLAAN DAN PENGEMBANGAN SISTEM INFORMASI BERBASIS AUDITOR INTERNAL - Dwi Ratnaningtias (Mount Hope Economic Global Journal, 2023)
The purpose of this research is to analyze the role of the Regional Inspectorate of Ogan Ilir District as the Internal Auditor, in this case as the supervisor and consultant of the Organization of Regional Approaches in the Environment of the Ogan Illir District Government. Qualitative research methods are case studies. The results of the research show that partially the performance of the Government Internal Audit has contributed positively to the existing Regional Appliance Organization.